A comprehensive investigation of surface generation and material removal characteristics in ultrasonic vibration assisted grinding. (June 2019) - Zhou, Weihua; Tang, Jinyuan; Chen, Haifeng; Shao, Wen
Highlights: A new model for predicting the surface topography and surface roughness in ultrasonic vibration assisted grinding is established, which takes the Poisson effect into consideration. A new method of calculating the undeformed chip thickness and dynamitic active grain number in ultrasonic vibration assisted grinding is established. The surface topography is predicted accurately by comparing experimental results. The different influences of imposed axial vibration and additional radial vibration due to Poisson effect on surface topography and undeformed chip thickness as well as dynamitic active grains are studied. Abstract: Ultrasonic vibration assisted grinding (UVAG) has been proved to be superior in improved machining quality and reduced surface roughness compared with conventional grinding (CG), but its mechanism is still in constant research and understanding. Except for the imposed axial vibration, another much smaller radial vibration is generated due to Poisson effect at the same time, which has different effect on the surface generation. In this paper, a comprehensive simulation model of UVAG considering Poisson effect has been developed to predict the three-dimensional surface topography and calculate the parameters (undeformed chip thickness, dynamic active grain number) which could reflect the characteristics of corresponding material removal process. The comparison between experimental results and simulated results shows that the method proposed in this paper is in good agreement with the experimental results. The imposed axial vibration can increase dynamic active grain number, generate uniform undeformed chip thickness and reduce the surface roughness, while the additional radial vibration causes the fluctuation of undeformed chip thickness and the increase of surface roughness. The proposed simulation model of UVAG provides a new approach to the prediction of the ultrasonic surface topography and understanding of material removal process as well as the optimization of the UVAG.